The poverty of power : energy and the economic crisis - Commoner, Barry, 1917- (New York : Knopf : distributed by Random House, 1976)
"In the last ten years, the United States'the most powerful and technically advanced society in human history'has been confronted by a series of ominous, seemingly intractable crises. First there was the threat to the environmental survival; then there was the apparent shortage of energy: and now there is the unexpected decline of the economy. These are usually regarded as separate afflictions, each to be solved in its own terms: environmental degradation by pollution controls; the energy crisis by finding new sources of energy and new ways of conserving it; the economic crisis by manipulating prices, taxes, and interest rates. But each effort to solve one crisis seems to clash with the solution of the others'pollution control reduces energy supplies; energy conservation jobs. Inevitably, proponents of one solution become opponents of the others. Policy stagnates and remedial action is paralyzed, adding to the confusion and gloom that beset the country." So opens Barry Commoner's The Poverty of Power, the book in which America's great biologist and environmentalist addresses himself to the central question of our day. He concludes that "what confronts us is not a series of separate crises, but a single basic deficit'a fault that lies deep in the design of modern society. This book is an effort to unearth that fault, to trace its relation to the separate crises, and to consider what can be done to correct it at its root."
Includes bibliographical references and index.
Keywords: Power resources; Power (Mechanics); Energy policy -- United States; Economic history; United States -- Economic policy -- 1971-1981.